Effect of mixed Lactobacillus on the physicochemical properties of cloudy apple juice with the addition of polyphenols-concentrated solution. (June 2021) - Han, Mengzhen; Wang, Xiaowei; Zhang, Meina; Ren, Yaopeng; Yue, Tianli; Gao, Zhenpeng
Abstract: This study aimed to develop a functional apple juice with hypoglycemic and hypolipidemic properties. Cloudy apple juice (CAJ), cloudy apple juice with added polyphenol-concentrate solution (CAJP), and fermented cloudy apple juice with added polyphenol-concentrate solution (FCAJP) were prepared sequentially. Then the polyphenol profiles, organic acids, soluble sugars, flavor components, and sensory qualities of the three apple juices were determined. In addition, the potential hyperglycemic and hypolipidemic properties of the three kinds of apple juice were evaluated in vitro . The results revealed that the addition of polyphenol-concentrate solution derived from apple pomace significantly increased the flavonoids in CAJ and the capacity of CAJ to bind to bile salts. The levels of organic acids such as acetic acid, l -lactic acid, phenolic acids including chlorogenic acid and gallic acid, and volatile compounds increased during fermentation. Inhibition of α-glucosidase was dose-dependent. The fermented CAJP showed the best inhibition (>99% at 50 μL). Furthermore, all juice samples were rated as acceptable by consumers. Highlights: The addition of polyphenols-concentrated solution increased the flavonoids in CAJ. Phenolic acids increased significantly after fermentation. FCAJP showed best α-glycosidase inhibitory activity. Three kinds of apple juice had potential to bind bile salts.